2019
DOI: 10.12783/dtetr/cemms2019/32026
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of PPP Model Based on Fault Tree Model for Urban Underground Utility Tunnel

Abstract: The application of PPP mode in urban underground utility tunnel project has been vigorously promoted and popularized in China. However, the degree of project promotion varies greatly in different regions, and the enthusiasm of social capital to participate in projects varies. In essence, the impact of project risks cannot be ignored. Using the fault tree model to analyze the factors that affect the risk of PPP mode in the urban underground utility tunnel project, and obtains five factors which have great influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Canto-Perello et al proposed an expert system combining colour-coded, Delphi and hierarchical analysis methods to analyse the criticality and threat of integrated pipe corridors, which was used to support the planning of safety policies for urban underground facilities [16]; Jang and Jung investigated gas leaks and unknown ignitions in integrated pipe corridors due to gas explosions [17]; Wang and Fang constructed a risk evaluation model for integrated pipe corridor PPP projects, identified risk factors for utility based on a questionnaire survey, and then designed a risk evaluation index system and used an optimized fuzzy integrated rating method for risk evaluation [18]; He et al proposed a new fire risk assessment method within integrated pipe corridors in In the absence of historical cable fire data, fuzzy theory was used to calculate the failure probability of the main events of cable fires, and fuzzy inference was performed using a weighted fuzzy Petri net, and a numerical simulation method was used to quantify the losses caused by cable fires so as to quantify the risk of cable fires [19]; Ding et al applied a fault tree model to influence the urban underground integrated pipeline corridor project PPP model risks were analyzed, resulting in factors that have a greater impact on project risks, and found that the application of the PPP model in integrated underground corridors is more suitable for developed regions [20]; while the literature [21,22] analyzed the key risks of urban integrated corridors and their ratings from the actual situation of Chinese as well as Korean cities, respectively.…”
Section: Status Of Research Abroadmentioning
confidence: 99%
“…Canto-Perello et al proposed an expert system combining colour-coded, Delphi and hierarchical analysis methods to analyse the criticality and threat of integrated pipe corridors, which was used to support the planning of safety policies for urban underground facilities [16]; Jang and Jung investigated gas leaks and unknown ignitions in integrated pipe corridors due to gas explosions [17]; Wang and Fang constructed a risk evaluation model for integrated pipe corridor PPP projects, identified risk factors for utility based on a questionnaire survey, and then designed a risk evaluation index system and used an optimized fuzzy integrated rating method for risk evaluation [18]; He et al proposed a new fire risk assessment method within integrated pipe corridors in In the absence of historical cable fire data, fuzzy theory was used to calculate the failure probability of the main events of cable fires, and fuzzy inference was performed using a weighted fuzzy Petri net, and a numerical simulation method was used to quantify the losses caused by cable fires so as to quantify the risk of cable fires [19]; Ding et al applied a fault tree model to influence the urban underground integrated pipeline corridor project PPP model risks were analyzed, resulting in factors that have a greater impact on project risks, and found that the application of the PPP model in integrated underground corridors is more suitable for developed regions [20]; while the literature [21,22] analyzed the key risks of urban integrated corridors and their ratings from the actual situation of Chinese as well as Korean cities, respectively.…”
Section: Status Of Research Abroadmentioning
confidence: 99%
“…Risk evaluation: in the research on risk evaluation of integrated pipeline corridors, Canto-Perello et al proposed an expert system combining color-coding, Delphi, and hierarchical analysis methods to analyze the criticality and threat of integrated pipeline corridors, which was used to support the planning of safety policies for urban underground facilities [14]; Jang et al studied the risk of gas leakage and unknown ignition in integrated pipeline corridors due to gas explosions [4]; Wang et al constructed a risk evaluation model for integrated pipe corridor PPP projects, identified risk factors for utility based on a questionnaire survey, and then designed a risk evaluation index system and used an optimized fuzzy integrated rating method for risk evaluation [15]; He et al proposed a new fire risk assessment method within integrated pipe corridors in the absence of historical cable fire data, fuzzy theory was used to calculate the failure probability of the main events of cable fires, fuzzy inference was performed using a weighted fuzzy Petri net, and a numerical simulation method was used to quantify the losses caused by cable fires so as to quantify the risk of cable fires [16]; Ding et al applied a fault tree model to influence the urban underground integrated pipeline corridor project PPP model risk and concluded that the project risk has a greater impact on the factors and found that the application of the PPP model in underground integrated pipeline corridors is more suitable for developed regions [17]; Zhou et al and Seong et al, on the other hand, analyzed the key risks of urban integrated pipeline corridors and their ratings from the actual situation of Chinese as well as Korean cities, respectively. As early as 2011, Sousa et al proposed a method to systematically access and manage tunnel-related risks by combining a geological prediction model with a construction strategy decision model to predict the geology prior to tunnel construction to select the least risky construction strategy among different construction strategies [18]; Golam et al proposed a Bayesian belief network for assessing the risk of failure of metal water pipes model that can rank water supply trunk pipes in distribution networks to identify vulnerable and sensitive pipes for rational water supply management [19]; Zhang et al proposed a method for tunnel fire safety risk analysis based on fuzzy Bayesian networks [20]; Khwaja et al proposed a new public-private partnership based on fuzzy integral infrastructure project (PPP project) risk assessment method to help stakeholders make risk management decisions [21]; Wu et al developed a cloud model-based risk assessment model for shield construction in underground tunnels, which effectively addressed the stochastic uncertainty and fuzzy uncertainty of indicator factors [22]; in addition to these, the literature [23][24][25] also implemented dynamic analysis for underground tunnels and subsea tunnels; and the dynamic analysis of cable risks was realized.…”
Section: Related Workmentioning
confidence: 99%